Journal of Oceanography edited by The Oceanographic Society of Japan - Ebuchi, Naoto; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The Journal of Oceanography is the official journal of the Oceanographic Society of Japan and open to all oceanographers in the world. The main aim of the journal is to promote understandings of ocean systems from various aspects including physical, chemical, biological, geological oceanography as well as paleoceanography, etc. The journal welcomes research focusing on the western North Pacific and Asian coastal waters, but the study region is not limited to the Asian Pacific. The journal publishes original articles, short contributions, reviews, and correspondence in oceanography and related fields. Papers describing important new techniques, methods, and apparatuses will also be considered. Descriptive work will, however, be accepted if they contain general principles. Authors should submit their manuscripts online. Electronic submission substantially reduces the editorial processing and reviewing times and shortens overall publication times. Please go to http://www.springer.com/10872 for submission and for a full guide for authors.
Keywords: Oceanography; Aquatic ecology; Oceanography; Freshwater & Marine Ecology